Oxygen isotope composition of megacrysts from the Monastery kimberlite - Van Blerk, Joshua (Department of Geological Sciences, 2025)
Kimberlite megacrysts are large (>1 cm diameter) crystals that are thought to have crystallized from sub lithospheric proto-kimberlite melts near the base of the subcontinental lithospheric mantle (SCLM) during complex melt-SCLM interactions. Thus, these megacrysts represent an excellent opportunity to constrain the effects of SCLM assimilation on the δ18O values of primary mantle-derived melts. Laser fluorination δ 18O values for a well-characterized suite of megacrysts from the Monastery kimberlite, South Africa, are presented to: (1) constrain the δ18O value of the mantle source and (2) evaluate the effects of melt-SCLM interactions on the δ18O value of mantle-derived magmas. The Monastery kimberlite megacryst assemblages are as follows (in order of crystallization): (1) gt + cpx + opx + Fe-poor ol; (2) gt + cpx + opx + Group 1 ilm (Cr-, Mg-poor); (3) Group 2 ilm (Cr-rich, Mg-poor) + phlog; (4) Group 2 ilm + phlog + zir; (5) Group 2 ilm + phlog + zir + Fe-rich ol; and (6) Group 3 ilm (Cr and Mg-rich) + calcic cpx. The δ18O values of the megacrysts from the initial assemblage are: δ18Ogt = 5.12 and 5.25‰ (n = 2); δ18Ocpx = 4.72 and 5.02‰ (n = 2); δ18Oopx = 5.20 and 5.55‰ (n = 2); δ18OFe-poor ol = 5.43- 5.84‰ (x̄ = 5.23‰, σ = 0.10, n = 10), all showing no correlation between δ18O values and major element compositions. This implies that these megacrysts were in equilibrium with a melt of mantle-like δ18O values. The Group 1 ilmenites have δ18O values expected for mantle ilmenites, ranging from 3.88-4.35‰ (x̄ = 4.10‰, σ = 0.15, n = 8) (also in equilibrium with a melt of mantle-like δ18O values). They show a weak positive correlation between the δ18O value and Cr#, and no correlation with Mg#. In contrast, the δ18O values of the megacrysts from assemblages three to five implies that they were in equilibrium with a melt of δ18O values below the expected mantle-like range: δ18OGroup 2 ilm = 2.74-4.46‰ (x̄ = 3.56‰, σ = 0.45, n = 11); δ18Ophlog = 4.25-5.73‰ (x̄ = 5.08‰, σ = 0.48, n = 8); δ18Ozir = 4.87-5.09‰ (x̄ = 4.98‰, σ = 0.08, n = 6); and δ18OFe rich ol = 4.53-4.94‰ (x̄ = 4.75‰, σ = 0.15, n = 5). The Group 2 ilmenites show no correlations between the δ 18O value and Mg# and Cr#. The Fe-rich olivines show positive correlations with Mg# and Ni. The phlogopites show no correlations with the major element compositions. The Group 3 ilmenites have δ18O values ranging from 2.93-4.05‰ (x̄ = 3.59‰, σ = 0.36, n = 7). These are below the δ18O values expected for mantle ilmenites, but are slightly higher than the Group 2 ilmenites. The Group 3 ilmenites show a positive correlation between the δ18O value and Mg# and no correlation of δ18O with Cr#. The δ18O values of primary mantle-derived magmas are ~5.7‰ (Eiler, 2001) unless recycled crust is present in the source or if the magma assimilates crustal material en route to the surface. The variations in the δ18O values throughout the megacryst suite suggest that the parent melt underwent open system evolution in the SCLM. It is proposed that the Monastery proto-kimberlite originated from a convecting mantle source with a mantle-like δ18O value of ~5.33‰, which experienced two stages of evolution involving fractional crystallization and assimilation/melt-wall rock interaction. The low δ18O values in the phlogopites, zircons, Fe-rich olivines, and especially the Group 2 ilmenites (as low as ~4.25‰) can be explained by the assimilation most likely of low-δ18O eclogite (first stage evolution). The increased Cr# in the melt marked by the Group 2 ilmenites suggests the assimilation of Cr-rich pyroxenite veins. The Group 3 ilmenites give increased equilibrium melt-δ18O values of up to ~5.56‰ and give increased Mg# relative to the Group 2 iii ilmenites, which may be explained by the assimilation of Mg-rich metasomatized peridotite (second stage evolution).